The Trump phenomenon : how the politics of populism won in 2016 - Kivisto, Peter, 1948- (Society now., 2017)
On November 8, 2016, American voters elected Donald J. Trump to become the 45th President of the United States. Peter Kivisto analyses how this happened, focusing on who Trump is, who his supporters are, and the role of the media, right-wing Christians and the Republican Party in making Trump's victory possible. The book concludes with an analysis.